توظيف نظرية التأطير الإعلامي في حساب "إسرائيل في الخليج" على "تويتر" للإستمالات الإقناعية في الترويج السياحي لمناطق الداخل الفلسطيني المحتل - دانا سهيل عوض (My University, 2024)
Abstract This study aims to identify the topics, persuasive strategies, and framing mechanisms used in the "Israel in the Gulf" Twitter account to promote tourism in the occupied Palestinian territories. The study adopts a descriptive-analytical methodology, aligning closely with both quantitative and qualitative survey studies. The study population consists of all tweets from the "Israel in the Gulf" page, the official account of the virtual Israeli embassy in the Gulf countries. The study sample comprises tweets that focus on promoting tourism in all its forms on the "Israel in the Gulf" Twitter account during the period from June 29, 2021, to August 31, 2022. This timeframe was chosen due to changes that occurred, allowing travel between some Gulf Arab countries and Israel. Additionally, it coincided with aviation agreements that facilitated travel procedures, as well as Israel's declaration of its readiness to welcome tourists from the Gulf countries, particularly after the signing of the normalization agreement known as the "Abraham Accords." The study yielded several key results, including the prominence of emotional appeals used by the "Israel in the Gulf" Twitter account. The account utilized various emotional appeals, and its framing mechanisms aimed to employ persuasive strategies through tweets to promote tourism in the occupied Palestinian territories, notably utilizing the "Humanitarian Principles" frame. Keywords: Media Framing Theory, Israel in the Gulf, Twitter, Persuasive Appeals, Tourism Promotion, Occupied Palestinian Territories.